High-performance lithium ion capacitor negative electrode material and preparation method thereof
By introducing nitrogen-doped carbon and carbon nanotubes into the loaded materials of molybdenum disulfide, a three-dimensional conductive network structure is solved, and the problem of phase change and volume expansion of molybdenum disulfide during charging and discharge is improved, and the battery or Capacitance and cycling performance of capacitors.
Patent Information
- Application Number
- CN202411401679.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-02-07
AI Technical Summary
Molybdenum disulfide is prone to phase change and volume expansion during charging and discharging, resulting in slowing down the ion diffusion rate and rapid attenuation of capacity.
Using a loaded molybdenum disulfide, including a reduced graphene oxide support and a modified molybdenum disulfide supported thereon, the modified molybdenum disulfide consists of molybdenum disulfide and nitrogen-doped carbon, and nitrogen-doped carbon is inserted into the molybdenum disulfide. Carbon nanotubes are filled between the layers of the loaded molybdenum disulfide to form a three-dimensional conductive network structure.
Effectively reduce the volume changes of electrode material and structural collapse during charging and discharging, improve structural stability and conductivity, and improve the capacity and cycling performance of secondary batteries or capacitors.
Smart Images

Figure CN119400602A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of electrode materials, and in particular to negative electrode active materials and preparation methods, negative electrode plates, secondary batteries or capacitors, and electric energy storage systems. Background Art
[0002] Secondary batteries have the characteristics of high energy density, high average output voltage, low self-discharge, and no memory effect, and are widely used in electric vehicles, large energy storage equipment and other fields. In the structure of secondary batteries, the negative electrode active material is one of the important components, which has an important influence on the performance of the battery. Capacitors are asymmetric energy storage devices that use a combination of capacitor materials and battery materials as positive and negative electrodes, and thus have both the high power density of capacitors and the high energy density of batteries. However, the kinetic mismatch between the positive and negative electrodes caused by asymmetric electrode materials will affect the specific capacity and rate performance of lithium-ion capacitors, hindering the development of lithium-ion capacitors. In the structure of capacitors, the negative electrode active material also has a significant impact on the performance of capacitors.
[0003] Among the negative electrode active materials, the theoretical capacity of molybdenum disulfide (MoS2) material is as high as 670mAh / g. It has a two-dimensional layered structure similar to that of graphite negative electrode, and its larger interlayer spacing (0.62nm) creates conditions for the rapid transmission of ions. However, due to the poor conductivity of molybdenum disulfide, it is prone to phase change and volume expansion during repeated insertion and extraction, which can easily lead to problems such as slow ion diffusion rate and rapid capacity decay. Summary of the invention
[0004] Based on this, the present application provides a negative electrode active material and preparation method, a negative electrode plate, a secondary battery or capacitor, and an electric energy storage system. The negative electrode active material provided in the present application can effectively alleviate the problems of volume change and structural collapse of the electrode material during charging and discharging, improve structural stability and conductivity, and thus effectively improve the capacity and cycle performance of the secondary battery or capacitor.
[0005] In a first aspect of the present application, there is provided a negative electrode active material, comprising supported molybdenum disulfide and carbon nanotubes;
[0006] The supported molybdenum disulfide comprises a reduced graphene oxide carrier and modified molybdenum disulfide supported on the reduced graphene oxide carrier, wherein the modified molybdenum disulfide comprises molybdenum disulfide and nitrogen-doped carbon, the molybdenum disulfide has a layered structure, and the nitrogen-doped carbon is inserted between the layers of the molybdenum disulfide;
[0007] Among them, at least part of the interlamellar space of the supported molybdenum disulfide is filled with carbon nanotubes; the reduced graphene oxide carrier and the carbon nanotubes have etched holes.
[0008] In one embodiment, the carbon nanotubes filled between the layers of the supported molybdenum disulfide are a three-dimensional network structure, and the three-dimensional network structure is formed by a plurality of carbon nanotubes entangled with each other.
[0009] Wherein, the three-dimensional network structure of the carbon nanotubes is located between the sheets of the reduced graphene oxide carrier.
[0010] In one embodiment, the etched holes of the reduced graphene oxide carrier are obtained by etching the reduced graphene oxide or graphene oxide with an etchant; and / or,
[0011] The etched holes of the carbon nanotubes are obtained by etching the carbon nanotubes with an etchant.
[0012] In one embodiment, the negative electrode active material has one or more of the following characteristics:
[0013] (1) The diameter of the carbon nanotubes is 10 nm to 20 nm, and the length of the carbon nanotubes is 5 μm to 15 μm;
[0014] (2) The number of layers of the reduced graphene oxide carrier is 1 to 5;
[0015] (3) The pore volume of the negative electrode active material is 0.1 m 3 / g~0.5m 3 / g;
[0016] (4) The specific surface area of the negative electrode active material is 30 m 2 / g~90m 2 / g;
[0017] (5) The pore size of the negative electrode active material is 1 nm to 100 nm.
[0018] The second aspect of the present application provides a method for preparing the negative electrode active material according to any one of the embodiments of the first aspect of the present application, comprising the following steps:
[0019] Mixing graphene oxide, carbon nanotubes and an etchant in a first solvent, and performing etching treatment so that the graphene oxide and the carbon nanotubes have etched holes, thereby preparing a modified carbon material;
[0020] Mixing a molybdenum source, a sulfur source and a carbon-containing surfactant in a second solvent to prepare a molybdenum disulfide precursor solution;
[0021] The modified carbon material and the molybdenum disulfide precursor solution are mixed, and the pH is adjusted to 2 to 4 to prepare an acidified precursor solution;
[0022] The acidified precursor solution is subjected to a hydrothermal reaction, and after freeze-drying, a composite material to be carbonized is prepared; the composite material to be carbonized comprises a supported molybdenum disulfide precursor and carbon nanotubes; the supported molybdenum disulfide precursor comprises a graphene oxide carrier and a modified molybdenum disulfide precursor supported on the graphene oxide carrier, the modified molybdenum disulfide precursor comprises molybdenum disulfide and a carbon-containing surfactant, the molybdenum disulfide has a layered structure, and the carbon-containing surfactant is inserted between the layers of the molybdenum disulfide; at least part of the interlamellar space of the supported molybdenum disulfide is filled with carbon nanotubes;
[0023] The composite material to be carbonized is subjected to carbonization treatment in a nitrogen atmosphere, so that the graphene oxide is converted into reduced graphene oxide, and the carbon-containing surfactant is converted into nitrogen-doped carbon, so as to prepare the negative electrode active material.
[0024] In one embodiment, the step of preparing the molybdenum disulfide precursor solution satisfies one or more of the following characteristics:
[0025] (1) The molybdenum source includes ammonium tetrathiomolybdate,
[0026] (2) The sulfur source includes thiourea;
[0027] (3) The carbon-containing surfactant includes polyvinyl pyrrolidone;
[0028] (4) The mass ratio of the molybdenum source, the sulfur source and the carbon-containing surfactant is (145-160): (40-50): (30-45).
[0029] In one embodiment, the preparation method has one or more of the following characteristics:
[0030] (1) The process parameters of the hydrothermal reaction include: a reaction temperature of 200° C. to 220° C.;
[0031] (2) The freeze-drying process parameters include: a temperature of -45°C to -20°C;
[0032] (3) The process parameters of the carbonization treatment include: a reaction temperature of 830°C to 870°C;
[0033] (4) The diameter of the carbon nanotube is 10 nm to 20 nm, and the length of the carbon nanotube is 5 μm to 15 μm;
[0034] (5) The etchant includes one or more of sodium hydroxide and potassium hydroxide;
[0035] (6) The mass ratio of the graphene oxide, the carbon nanotubes and the etchant is (22-26): (2-12): (80-95).
[0036] In a third aspect of the present application, there is provided a negative electrode sheet, comprising a negative electrode current collector and a negative electrode active material layer stacked on the surface of the negative electrode current collector, wherein the negative electrode active material layer comprises the negative electrode active material according to any one of the embodiments of the first aspect of the present application;
[0037] Wherein, in terms of mass percentage, the negative electrode active material accounts for 70% to 85% of the negative electrode active material layer.
[0038] In a fourth aspect of the present application, a secondary battery or capacitor is provided, comprising a negative electrode, a positive electrode, a separator between the negative electrode and the positive electrode, and an electrolyte; wherein the negative electrode is the negative electrode sheet described in the third aspect of the present application;
[0039] The secondary battery is a lithium ion battery, a sodium ion battery, a potassium ion battery, a calcium ion battery, a magnesium ion battery or a zinc ion battery;
[0040] The capacitor is a lithium ion capacitor, a sodium ion capacitor, a potassium ion capacitor, a calcium ion capacitor, a magnesium ion capacitor or a zinc ion capacitor.
[0041] In a fifth aspect of the present application, an electric energy storage system is provided, comprising an energy storage unit, wherein the energy storage unit comprises the capacitor described in the fourth aspect of the present application.
[0042] This application has the following beneficial effects:
[0043] In the negative electrode active material provided by the present application, the carrier of the supported molybdenum disulfide is reduced graphene oxide with etched holes, which can ensure the growth of modified molybdenum disulfide, and the reduced graphene oxide is beneficial to provide a conductive path for electrons, thereby improving the conductivity of the negative electrode active material; the supported material of the supported molybdenum disulfide is modified molybdenum disulfide, the introduction of molybdenum disulfide can increase the battery capacity, and the intercalation structure of nitrogen-doped carbon can expand the interlayer spacing of molybdenum disulfide, which can further widen the ion transmission channel; further, carbon nanotubes are filled in at least part of the lamellae of the supported molybdenum disulfide, which together with the supported molybdenum disulfide form a three-dimensional conductive network structure, further improving the conductivity of the negative electrode active material and facilitating charge transmission during charging and discharging.
[0044] In summary, the negative electrode active material provided in the present application can effectively improve the capacity, cycle performance and rate performance of the secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 A schematic diagram of the structure of the negative electrode active material provided in this application;
[0046] Figure 2 This is a SEM image of the negative electrode active material prepared in the embodiment of the present application;
[0047] Figure 3 A nitrogen adsorption-desorption isotherm curve of the negative electrode active material prepared in Example 1 of the present application;
[0048] Figure 4 This is a pore size distribution diagram of the negative electrode active material prepared in Example 1 of the present application.
[0049] In the figure, 10-supported molybdenum disulfide, 101-reduced graphene oxide support, 102-modified molybdenum disulfide; 20-carbon nanotube. DETAILED DESCRIPTION
[0050] The following is a further complete and clear description of the negative electrode active material and preparation method thereof, the negative electrode plate, the secondary battery or capacitor, and the electric energy storage system of the present application in combination with specific embodiments. The present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.
[0051] See also Figure 1 In a first aspect of the present application, a negative electrode active material is provided, comprising supported molybdenum disulfide 10 and carbon nanotubes 20;
[0052] The supported molybdenum disulfide 10 includes a reduced graphene oxide carrier 101 and a modified molybdenum disulfide 102 supported on the reduced graphene oxide carrier 101, wherein the modified molybdenum disulfide includes molybdenum disulfide and nitrogen-doped carbon, the molybdenum disulfide has a layered structure, and the nitrogen-doped carbon is inserted between the layers of the molybdenum disulfide;
[0053] At least part of the interlamellar space of the supported molybdenum disulfide 10 is filled with carbon nanotubes 20;
[0054] Wherein, the reduced graphene oxide carrier and the carbon nanotube have etched holes.
[0055] In the negative electrode active material provided by the present application, the carrier of the loaded molybdenum disulfide is a reduced graphene oxide with etched holes, which can ensure the growth of modified molybdenum disulfide, and is conducive to providing more active sites, facilitating the adsorption and transmission of ions. The load of the loaded molybdenum disulfide is modified molybdenum disulfide, the introduction of molybdenum disulfide can increase the battery capacity, and the intercalation structure of nitrogen-doped carbon can expand the interlayer spacing of molybdenum disulfide, which can further widen the transmission channel of ions, and at the same time, the incorporation of nitrogen-doped carbon can effectively inhibit the volume expansion and structural collapse of molybdenum disulfide during the charge and discharge process, so as to further improve the structural stability; further, carbon nanotubes are filled in at least part of the loaded molybdenum disulfide sheet, which together with the loaded molybdenum disulfide forms a three-dimensional conductive network structure, further improving the conductivity of the negative electrode active material, which is conducive to charge transmission during the charge and discharge process; and the filling of carbon nanotubes can also buffer the volume change during the charge and discharge process. In summary, the negative electrode active material provided by the present application can effectively improve the capacity, cycle performance and rate performance of the secondary battery.
[0056] In one example, the etched holes of the reduced graphene oxide carrier are obtained by etching the reduced graphene oxide or graphene oxide with an etchant; and / or,
[0057] The etched holes of the carbon nanotubes are obtained by etching the carbon nanotubes with an etchant.
[0058] In one specific example, the etchant includes one or more of sodium hydroxide and potassium hydroxide.
[0059] In one example, the carbon nanotubes filled between the layers of the supported molybdenum disulfide are a three-dimensional network structure, and the three-dimensional network structure is formed by a plurality of carbon nanotubes entangled with each other.
[0060] Wherein, the three-dimensional network structure of the carbon nanotubes is located between the sheets of the reduced graphene oxide carrier.
[0061] The three-dimensional network structure formed by the carbon nanotubes entangled with each other can provide strong support for the entire negative electrode material, enhancing its mechanical strength and stability. During the charge and discharge process of the battery, it can better withstand the volume change and structural stress of the electrode material, reducing the breakage and damage of the electrode. At the same time, the three-dimensional network structure increases the path and contact points for electron transmission, further improving the overall conductivity of the electrode material. This helps electrons to transfer more quickly in the electrode, thereby improving the rate performance and charge and discharge efficiency of the battery. Furthermore, the three-dimensional network structure of carbon nanotubes filled between the reduced graphene oxide sheets can also prevent the reduced graphene oxide sheets from agglomerating, maintaining their good dispersion state, thereby giving full play to the advantages of reduced graphene oxide.
[0062] In one example, the molybdenum disulfide is a nanoflower-shaped molybdenum disulfide. At this time, the nitrogen-doped carbon is inserted between the sheets of the nanoflower-shaped molybdenum disulfide. It can be understood that the nitrogen-doped carbon is nitrogen-doped amorphous carbon.
[0063] In one example, the mass fraction of the supported molybdenum disulfide in the negative electrode active material is 89% to 99.5%. The mass fraction of the supported molybdenum disulfide includes but is not limited to 89%, 90%, 92%, 94%, 96%, 98%, 99% or 99.5%.
[0064] In one example, the mass fraction of the carbon nanotubes in the negative electrode active material is 0.5% to 11%, and the mass fraction of the carbon nanotubes includes but is not limited to 0.6%, 0.8%, 1%, 3%, 5%, 8%, 10% or 11%.
[0065] In one example, the mass fraction of the reduced graphene oxide carrier in the supported molybdenum disulfide is 7% to 25%. The mass fraction of the reduced graphene oxide carrier includes but is not limited to 8%, 9%, 11%, 15%, 18%, 20%, 23%, and 25%.
[0066] In one example, the mass fraction of the modified molybdenum disulfide in the supported molybdenum disulfide is 75% to 93%. The mass fraction of the modified molybdenum disulfide includes but is not limited to 78%, 80%, 82%, 85%, 88%, 90% or 93%.
[0067] The diameter and length of carbon nanotubes play an important role in ensuring their electrical conductivity, structural stability, specific surface area and other properties. In one example, the diameter of the carbon nanotubes is 10nm to 20nm, and the length of the carbon nanotubes is 5μm to 15μm. Specifically, the diameter of the carbon nanotubes includes but is not limited to 10nm, 12nm, 14nm, 16nm, 18nm or 20nm. The length of the carbon nanotubes includes but is not limited to 5μm, 8μm, 10μm, 12μm, 14μm or 15μm.
[0068] In one example, the number of layers of the reduced graphene oxide carrier is 1 to 5. Specifically, the number of layers of the reduced graphene oxide carrier includes but is not limited to 1, 2, 3, 4 or 5 layers.
[0069] In one example, the pore volume of the negative electrode active material is 0.1 cm 3 / g~0.5cm 3 / g. The negative electrode active material provided in the present application has a larger pore volume, indicating that it has more space to store ions, thereby increasing the specific capacity of the secondary battery; in addition, its larger pore volume is conducive to the electrolyte fully infiltrating the electrode material, increasing the contact area between the electrode and the electrolyte, and promoting the electrochemical reaction. Specifically, the pore volume of the negative electrode active material includes but is not limited to 0.1cm 3 / g, 0.2cm 3 / g, 0.28cm 3 / g, 0.29cm 3 / g, 0.3cm 3 / g, 0.31cm 3 / g, 0.35cm 3 / g, 0.4cm 3 / g or 0.5cm 3 / g.
[0070] In one example, the specific surface area of the negative electrode active material is 30 m 2 / g~90m 2 / g. The negative electrode active material provided in the present application has a high specific surface area, which means that it can provide more active sites, so that ions have more locations to be embedded and released during the charge and discharge process. Specifically, the specific surface area of the negative electrode active material includes but is not limited to 40m 2 / g, 50m 2 / g, 60m 2 / g, 70m 2 / g, 80m 2 / g, 81m 2 / g, 81.5m 2 / g, 82m 2 / g, 85m 2 / g or 90m 2 / g.
[0071] In one example, the pore size of the negative electrode active material is 1nm to 100nm. The pores in the negative electrode active material provided in the present application can provide suitable space for the storage of ions, buffer volume changes, reduce damage to the material structure, and improve cycle stability. Specifically, the pore size of the negative electrode active material includes but is not limited to 1nm, 2nm, 2.2nm, 2.3nm, 2.4nm, 2.5nm, 3nm, 5nm, 10nm, 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm or 100nm.
[0072] This application is to complete and refine the overall technical solution, better ensure the composition and specific structure of the negative electrode active material, and improve its electrochemical performance. The preparation method of the above composite active material can specifically include the following contents.
[0073] In a second aspect of the present application, there is provided a method for preparing the negative electrode active material as described in any example of the first aspect of the present application, comprising the following steps:
[0074] S10, mixing graphene oxide, carbon nanotubes and an etchant in a first solvent, and performing an etching process so that the graphene oxide and the carbon nanotubes have etched holes, thereby preparing a modified carbon material;
[0075] S20, mixing a molybdenum source, a sulfur source and a carbon-containing surfactant in a second solvent to prepare a molybdenum disulfide precursor solution;
[0076] S30, mixing the modified carbon material and the molybdenum disulfide precursor solution, adjusting the pH to 2 to 4, and preparing an acidified precursor solution;
[0077] S40, subjecting the acidified precursor solution to a hydrothermal reaction, and freeze-drying to prepare a composite material to be carbonized; the composite material to be carbonized comprises a supported molybdenum disulfide precursor and carbon nanotubes; the supported molybdenum disulfide precursor comprises a graphene oxide carrier and a modified molybdenum disulfide precursor supported on the graphene oxide carrier, the modified molybdenum disulfide precursor comprises molybdenum disulfide and a carbon-containing surfactant, the molybdenum disulfide has a layered structure, and the carbon-containing surfactant is inserted between the layers of the molybdenum disulfide; at least part of the interlamellar space of the supported molybdenum disulfide is filled with carbon nanotubes;
[0078] S50, carbonizing the composite material to be carbonized in a nitrogen atmosphere to convert the graphene oxide into reduced graphene oxide and the carbon-containing surfactant into nitrogen-doped carbon, thereby preparing the negative electrode active material.
[0079] The preparation method provided in the present application can realize the preparation of the negative electrode active material described in any example of the first aspect of the present application. The preparation process is simple and easy to realize industrial production. Furthermore, the above preparation method includes the steps of hydrothermal reaction, freeze drying and carbonization heat treatment. The above steps are combined with each other to enable the MoS2 nano flower balls to grow uniformly on the surface of graphene oxide, increase the structural stability and uniformity of the system; at the same time, the negative electrode active material is prepared with a nanostructure, which increases the specific surface area of the material and reduces the local current density.
[0080] In one example, in step S10, the diameter of the carbon nanotube is 10 nm to 20 nm, and the length of the carbon nanotube is 5 μm to 15 μm.
[0081] In one example, in step S10, the etchant includes one or more of sodium hydroxide and potassium hydroxide. Sodium hydroxide and potassium hydroxide have strong alkalinity, which can react with the functional groups on the surface of carbon nanotubes and graphene oxide to achieve an etching effect. Etched holes are introduced into the surface of the modified carbon material after etching, which increases the specific surface area of the carbon material and provides more active sites for it.
[0082] The content of the etchant plays an important role in optimizing the etching effect and ensuring the performance of the material after etching. In one example, in step S10, the mass ratio of the graphene oxide, the carbon nanotubes and the etchant is (22-26): (2-12): (80-95). Specifically, the mass ratio of the graphene oxide, the carbon nanotubes and the etchant includes but is not limited to 23.6:2:80, 23.6:12:88.5, 23.6:2.6:88.5, 23.6:2.8:88.5, 23.6:2.9:88.5, 23.6:5.6:88.5, 23.6:5.9:88.5, 23.6:6:88.5, 23.6:11:88.5, 23.6:11.8:88.5, 23.6:12:88.5, 24:12:90 or 25:12:95.
[0083] In one example, in step S10, the first solvent includes deionized water.
[0084] In one example, in step S10, the etching treatment is performed by stirring. Furthermore, the stirring time is 4 hours to 6 hours. After the etching treatment step, the modified carbon material is centrifuged, washed, and dried.
[0085] In one example, in step S20, the molybdenum source includes ammonium tetrathiomolybdate.
[0086] In one example, in step S20, the sulfur source includes thiourea.
[0087] In one example, in step S20, the carbon-containing surfactant includes polyvinyl pyrrolidone.
[0088] In one example, in step S20, the mass ratio of the molybdenum source, the sulfur source and the carbon-containing surfactant is (145-160): (40-50): (30-45). Specifically, the mass ratio of the molybdenum source, the sulfur source and the carbon-containing surfactant includes but is not limited to 150:40:37, 154:40:37, 154:46:30, 154:46:35, 154:46:37, 154:50:37, 160:50:37, 160:50:40 or 160:50:45.
[0089] Ammonium tetrathiomolybdate (NH4)2MoS4, thiourea CH4N2S and polyvinylpyrrolidone (PVP) react with each other. The specific molecular structure and functional groups of polyvinylpyrrolidone (PVP) can act as a template in the reaction system, guiding the growth and aggregation of molybdenum disulfide to form a specific nano-flower ball morphology. In this process, the polyvinylpyrrolidone (PVP) template agent is inserted between the layers of molybdenum disulfide, regulating the structure of molybdenum disulfide.
[0090] In one example, in step S30, the reagent for adjusting the pH to 2 to 4 is dilute sulfuric acid. Specifically, the concentration of the dilute sulfuric acid is 0.08 mol / L to 0.12 mol / L. More specifically, the pH value includes but is not limited to 2, 2.5, 2.8, 3, 3.2, 3.5, 3.8 or 4.
[0091] The temperature of the hydrothermal synthesis plays an important role in the structural formation of molybdenum disulfide. In one example, in step S40, the process parameters of the hydrothermal reaction include: the reaction temperature is 200°C to 220°C. Specifically, the time of the hydrothermal reaction is 8h to 12h. Specifically, the temperature for the hydrothermal reaction includes but is not limited to 200°C, 210°C, 215°C, 218°C or 220°C.
[0092] In one example, in step S40, the freeze-drying process parameters include: a temperature of -45°C to -20°C. Furthermore, the freeze-drying time is 24h to 36h. Specifically, the freeze-drying temperature includes but is not limited to -45°C, -40°C, -30°C or -20°C. Freeze-drying plays an important role in maintaining the stability of the structure and preventing deformation and collapse of the structure. If high-temperature thermal drying is used, at this time, the heating of molybdenum disulfide will cause its interlayer spacing to decrease, which will cause the carbon-containing surfactant inserted between its layers to escape.
[0093] In one example, in step S50, the process parameters of the carbonization treatment include: the reaction temperature is 830°C to 870°C. Furthermore, the time of the carbonization treatment is 3h to 4h. Specifically, the carbonization temperature includes but is not limited to 830°C, 840°C, 850°C, 860°C or 870°C. In the step of carbonization treatment, the carbon-containing surfactant inserted into the molybdenum disulfide layer will be carbonized, and nitrogen-doped carbon will be prepared under a nitrogen atmosphere. Its unique intercalation structure can expand the interlayer spacing of the molybdenum disulfide (002) surface, making ions easier to transmit. At the same time, nitrogen-doped carbon liquid can give carbon materials better conductivity.
[0094] In one specific example, the steps of preparing the negative electrode active material include:
[0095] S100, mixing graphene oxide, carbon nanotubes and an etchant in a mass ratio of (22-26): (2-12): (80-95) in deionized water, and performing etching treatment so that the graphene oxide and the carbon nanotubes have etched holes, thereby preparing a modified carbon material;
[0096] S200, ammonium tetrathiomolybdate, thiourea and polyvinyl pyrrolidone are mixed in deionized water at a mass ratio of (145-160): (40-50): (30-45) to prepare a molybdenum disulfide precursor solution;
[0097] S300, mixing the modified carbon material and the molybdenum disulfide precursor solution, using dilute sulfuric acid with a concentration of 0.08 mol / L to 0.12 mol / L, adjusting the pH to 2 to 4, and preparing an acidified precursor solution;
[0098] S400, subjecting the acidified precursor solution to a hydrothermal reaction at 200° C. to 220° C. for 8 h to 12 h, and freeze-drying at -45° C. to -20° C. for 24 h to 36 h to prepare a composite material to be carbonized;
[0099] S500, subjecting the composite material to be carbonized to a carbonization treatment in a nitrogen atmosphere at a temperature of 830° C. to 870° C. for a time of 3 h to 4 h, to prepare the negative electrode active material.
[0100] In a third aspect of the present application, a negative electrode sheet is provided, comprising a negative electrode current collector and a negative electrode active material layer stacked on the surface of the negative electrode current collector, wherein the negative electrode active material layer comprises the negative electrode active material described in any example of the first aspect of the present application.
[0101] In one example, the negative electrode active material accounts for 70% to 85% of the negative electrode active material layer by mass. Specifically, the negative electrode active material accounts for, but is not limited to, 67.5%, 70%, 72%, 75%, 78%, 80%, 82%, 83% or 85%.
[0102] In a more specific example, the negative electrode active material layer includes, by mass percentage, 70% to 85% of negative electrode active material, 7.5% to 15% of binder, and 7.5% to 15% of conductive agent.
[0103] For example, the conductive agent includes but is not limited to conductive carbon black. The binder includes but is not limited to polyvinylidene fluoride. By proportioning the components in the negative electrode active material layer, it is possible to ensure good adhesion between the active material and the current collector, while also maintaining its structural stability. Specifically, the mass percentage of the negative electrode active material includes but is not limited to 67.5%, 70%, 72%, 75%, 78%, 80%, 82%, 83% or 85%. The mass percentage of the binder includes but is not limited to 7.5%, 8%, 9%, 10%, 11%, 12% or 15%. The mass percentage of the conductive agent includes but is not limited to 7.5%, 8%, 9%, 10%, 11%, 12% or 15%.
[0104] In a fourth aspect of the present application, a secondary battery or capacitor is provided, comprising a negative electrode, a positive electrode, a separator between the negative electrode and the positive electrode, and an electrolyte; wherein the negative electrode is the negative electrode sheet described in the third aspect of the present application.
[0105] Specifically, the secondary battery is a lithium ion battery, a sodium ion battery, a potassium ion battery, a calcium ion battery, a magnesium ion battery or a zinc ion battery.
[0106] More specifically, the positive electrode, the separator and the electrolyte in the secondary battery are the positive electrodes, separators and electrolytes commonly used by those skilled in the art.
[0107] For example, the positive electrode in the secondary battery includes a positive electrode current collector and a positive electrode active material layer located on the positive electrode current collector. Specifically, the positive electrode current collector includes an aluminum foil current collector. Further, the composition of the positive electrode active material layer includes a positive electrode active material, a conductive agent and a binder. The positive electrode active material can be, for example, lithium cobalt oxide (LiCoO2), lithium nickel manganese cobalt ternary material, lithium manganese oxide (LiMn2O4), lithium nickel manganese oxide (LiNi 0.5 Mn 1.5 O4) and one or more of lithium iron phosphate (LiFePO4). For example, the conductive agent in the secondary battery includes one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers. The binder may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylate resin.
[0108] Without limitation, the diaphragm in the secondary battery can be selected from diaphragms used in secondary batteries, such as polyolefin films, including microporous films made of polyethylene and polypropylene; multilayer films of porous polyethylene films and polypropylene; non-woven fabrics formed by polyester fibers, aramid fibers, glass fibers, etc.; and substrates formed by ceramic particles such as silicon dioxide, aluminum oxide, and titanium dioxide attached to their surfaces. The electrolyte may include an electrolyte and a non-aqueous organic solvent. The electrolyte is preferably LiPF6, LiBF4, LiSbF6, and LiAsF6. The non-aqueous organic solvent may be a carbonate, ester, and ether. Among them, carbonates such as ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) may be preferably used.
[0109] Specifically, the capacitor is a lithium ion capacitor, a sodium ion capacitor, a potassium ion capacitor, a calcium ion capacitor, a magnesium ion capacitor or a zinc ion capacitor.
[0110] More specifically, the positive electrode, the separator and the electrolyte in the capacitor are all positive electrodes, separators and electrolytes commonly used by those skilled in the art.
[0111] For example, the positive electrode in the capacitor includes a positive electrode current collector and a positive electrode active material layer located on the positive electrode current collector. Specifically, the positive electrode current collector includes an aluminum foil current collector. Further, the composition of the positive electrode active material layer includes a positive electrode active material, a conductive agent and a binder. The positive electrode active material may be, for example, a porous carbon-based material or a conductive polymer, wherein the porous carbon-based material is activated carbon fiber, activated carbon powder, carbon nanotube or graphene, or a mixture of one of lithium iron phosphate, lithium iron manganese phosphate, lithium nickel cobalt manganate, lithium nickel manganate, lithium nickel cobalt aluminum oxide, lithium manganate, lithium nickel oxide, lithium nickel oxide, lithium nickel cobalt manganese aluminum oxide or lithium cobalt oxide and one of activated carbon fiber, activated carbon powder, carbon nanotube or graphene; the conductive polymer is polyaniline, polypyrrole or polythiophene and its derivatives; the conductive agent is graphene, carbon nanotube, conductive carbon black, graphite conductive agent, carbon fiber conductive agent; the binder is polyvinyl alcohol (PVA), polytetrafluoroethylene (PTFE), sodium carboxymethyl cellulose (CMC), olefins, polyvinylidene fluoride / N-methylpyrrolidone (PVDF / NMP).
[0112] The diaphragm in the capacitor includes but is not limited to a microporous membrane made of polyethylene or polypropylene, a Celgard diaphragm or a fiber paper diaphragm. The electrolyte in the capacitor may include an electrolyte and a non-aqueous organic solvent. The electrolyte is preferably LiPF6, LiBF4, LiSbF6, or LiAsF6. The non-aqueous organic solvent may be a carbonate, an ester, or an ether. Among them, carbonates such as ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) may be preferably used.
[0113] In a fifth aspect of the present application, an electric energy storage system is provided, comprising an energy storage unit, wherein the energy storage unit comprises the capacitor described in the fourth aspect of the present application.
[0114] The following further specific examples are provided to explain the present application in detail. It should also be understood that the following examples are only used to further explain the present application and cannot be understood as limiting the scope of protection of the present application. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present application belong to the scope of protection of the present application. The specific process parameters of the following embodiments are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not necessarily limited to the specific values of the embodiments below.
[0115] Example 1
[0116] Embodiment 1 provides a method for preparing a negative electrode active material, comprising the following steps:
[0117] (1) placing 23.6 mg of graphene oxide (1-5 layers) and 5.9 mg of carbon nanotubes (tube diameter 10-20 nm, tube length 5-15 μm) in deionized water and ultrasonically dispersing them for 3 h; then adding 88.5 mg of sodium hydroxide and stirring for 5 h to perform etching treatment so that the graphene oxide and the carbon nanotubes have etched holes, centrifuging and washing, to prepare etched graphene oxide and etched carbon nanotubes;
[0118] (2) 154 mg of ammonium tetrathiomolybdate was placed in deionized water, stirred for 3 h, and then 46 mg of thiourea and 37 mg of polyvinyl pyrrolidone were added, and stirred for 3 h to prepare a molybdenum disulfide precursor solution;
[0119] (3) placing the etched graphene oxide and the etched carbon nanotubes in step (1) in deionized water and stirring for 3 h, then mixing with the molybdenum disulfide precursor solution in step (2), dropping 0.1 mol / L dilute sulfuric acid, adjusting the pH to 3, and preparing an acidified precursor solution;
[0120] (4) pouring the acidified precursor solution of step (3) into a reaction kettle, performing a hydrothermal reaction at 220° C. for 8 h to obtain a black solid; washing the black solid with deionized water three times, and then freeze-drying it at -45° C. for 24 h to prepare a composite material to be carbonized;
[0121] (5) The composite material to be carbonized is subjected to carbonization treatment in a nitrogen atmosphere at a temperature of 850° C. for 3 h to prepare the negative electrode active material. The SEM image of the negative electrode active material is shown in FIG. Figure 2 The nitrogen adsorption and desorption isotherm of the negative electrode active material in Example 1 is shown in Figure 3 The pore size distribution diagram is shown in Figure 4 shown.
[0122] Figure 2 The wrinkled sheet structure of (a) corresponds to reduced graphene oxide. It can be seen that a large number of white particles, which are molybdenum disulfide, are loaded on the reduced graphene oxide. Figure 2 In (b), it can be seen that the carbon nanotubes are cross-linked to form a three-dimensional network structure, and they are located between the sheets of partially reduced graphene oxide.
[0123] Figure 3 It can be seen that the N2 adsorption-desorption curve shows a typical IV type isotherm and has an obvious hysteresis loop, which means that the material has typical mesoporous characteristics. The H3 type hysteresis loop shows that the pores are slits formed by stacking of flaky particles. The BET calculated specific surface area of the negative electrode active material is 81.83 m 2 / g. In addition, Figure 4 The existence of mesopores can also be further proved. The pore size of the negative electrode active material is concentrated around 2.36nm. The pore volume of the negative electrode active material calculated by BJH is 0.29cm 3 / g.
[0124] Example 2
[0125] Embodiment 2 provides a method for preparing a negative electrode active material, comprising the following steps:
[0126] (1) placing 23.6 mg of graphene oxide (1-5 layers) and 11.8 mg of carbon nanotubes (tube diameter 10-20 nm, tube length 5-15 μm) in deionized water and ultrasonically dispersing them for 3 h; then adding 88.5 mg of sodium hydroxide and stirring for 5 h to perform etching treatment so that the graphene oxide and the carbon nanotubes have etched holes, centrifuging and washing, to prepare etched graphene oxide and etched carbon nanotubes;
[0127] (2) 154 mg of ammonium tetrathiomolybdate was placed in deionized water, stirred for 3 h, and then 46 mg of thiourea and 37 mg of polyvinyl pyrrolidone were added, and stirred for 3 h to prepare a molybdenum disulfide precursor solution;
[0128] (3) placing the etched graphene oxide and the etched carbon nanotubes in step (1) in deionized water and stirring for 3 h, then mixing with the molybdenum disulfide precursor solution in step (2), dropping 0.1 mol / L dilute sulfuric acid, adjusting the pH to 3, and preparing an acidified precursor solution;
[0129] (4) pouring the acidified precursor solution of step (3) into a reaction kettle, performing a hydrothermal reaction at 220° C. for 8 h to obtain a black solid; washing the black solid with deionized water three times, and then freeze-drying it at -45° C. for 24 h to prepare a composite material to be carbonized;
[0130] (5) The composite material to be carbonized is subjected to a carbonization treatment in a nitrogen atmosphere at a temperature of 850° C. for 3 h to prepare the negative electrode active material.
[0131] Example 3
[0132] Embodiment 3 provides a method for preparing a negative electrode active material, comprising the following steps:
[0133] (1) placing 23.6 mg of graphene oxide (1-5 layers) and 2.9 mg of carbon nanotubes (tube diameter 10-20 nm, tube length 5-15 μm) in deionized water and ultrasonically dispersing them for 3 h; then adding 88.5 mg of sodium hydroxide and stirring for 5 h to perform etching treatment so that the graphene oxide and the carbon nanotubes have etched holes, centrifuging and washing, to prepare etched graphene oxide and etched carbon nanotubes;
[0134] (2) 154 mg of ammonium tetrathiomolybdate was placed in deionized water, stirred for 3 h, and then 46 mg of thiourea and 37 mg of polyvinyl pyrrolidone were added, and stirred for 3 h to prepare a molybdenum disulfide precursor solution;
[0135] (3) placing the etched graphene oxide and the etched carbon nanotubes in step (1) in deionized water and stirring for 3 h, then mixing with the molybdenum disulfide precursor solution in step (2), dropping 0.1 mol / L dilute sulfuric acid, adjusting the pH to 3, and preparing an acidified precursor solution;
[0136] (4) pouring the acidified precursor solution of step (3) into a reaction kettle, performing a hydrothermal reaction at 220° C. for 8 h to obtain a black solid; washing the black solid with deionized water three times, and then freeze-drying it at -45° C. for 24 h to prepare a composite material to be carbonized;
[0137] (5) The composite material to be carbonized is subjected to a carbonization treatment in a nitrogen atmosphere at a temperature of 850° C. for 3 h to prepare the negative electrode active material.
[0138] Comparative Example 1
[0139] Comparative Example 1 is substantially the same as Example 1, except that the step of etching the carbon nanotubes and graphene oxide is not included in Comparative Example 1, which is specifically as follows:
[0140] (1) placing 23.6 mg of graphene oxide (1-5 layers) and 5.9 mg of carbon nanotubes (tube diameter 10-20 nm, tube length 5-15 μm) in deionized water and ultrasonically dispersing for 3 h to prepare a first dispersion;
[0141] (2) 154 mg of ammonium tetrathiomolybdate was placed in deionized water, stirred for 3 h, and then 46 mg of thiourea and 37 mg of polyvinyl pyrrolidone were added, and stirred for 3 h to prepare a molybdenum disulfide precursor solution;
[0142] (3) mixing the first dispersion of step (1) and the molybdenum disulfide precursor of step (2), adding dilute sulfuric acid with a concentration of 0.1 mol / L, adjusting the pH to 3, and preparing an acidified precursor solution;
[0143] (4) pouring the acidified precursor solution of step (3) into a reaction kettle, performing a hydrothermal reaction at 220° C. for 8 h to obtain a black solid; washing the black solid with deionized water three times, and then freeze-drying it at -45° C. for 24 h to prepare a composite material to be carbonized;
[0144] (5) The composite material to be carbonized is subjected to a carbonization treatment in a nitrogen atmosphere at a temperature of 850° C. for 3 h to prepare the negative electrode active material.
[0145] Comparative Example 2
[0146] Comparative Example 2 is basically the same as Example 1, except that high temperature heat drying is used to replace freeze drying in Comparative Example 2. The specific steps are as follows:
[0147] (1) placing 23.6 mg of graphene oxide (1-5 layers) and 5.9 mg of carbon nanotubes (tube diameter 10-20 nm, tube length 5-15 μm) in deionized water and ultrasonically dispersing them for 3 h; then adding 88.5 mg of sodium hydroxide and stirring for 5 h to perform etching treatment so that the graphene oxide and the carbon nanotubes have etched holes, centrifuging and washing, to prepare etched graphene oxide and etched carbon nanotubes;
[0148] (2) 154 mg of ammonium tetrathiomolybdate was placed in deionized water, stirred for 3 h, and then 46 mg of thiourea and 37 mg of polyvinyl pyrrolidone were added, and stirred for 3 h to prepare a molybdenum disulfide precursor solution;
[0149] (3) placing the etched graphene oxide and the etched carbon nanotubes in step (1) in deionized water and stirring for 3 h, then mixing with the molybdenum disulfide precursor solution in step (2), dropping 0.1 mol / L dilute sulfuric acid, adjusting the pH to 3, and preparing an acidified precursor solution;
[0150] (4) pouring the acidified precursor solution of step (3) into a reaction kettle, performing a hydrothermal reaction at 220° C. for 8 h to obtain a black solid; washing the black solid with deionized water three times, and then placing it in an oven at 100° C. for 24 h for thermal drying to prepare a composite material to be carbonized;
[0151] (5) The composite material to be carbonized is subjected to a carbonization treatment in a nitrogen atmosphere at a temperature of 850° C. for 3 h to prepare the negative electrode active material.
[0152] Comparative Example 3
[0153] Comparative Example 3 is substantially the same as Example 1, except that no carbonization treatment is performed in Comparative Example 3. The specific steps are as follows:
[0154] (1) placing 23.6 mg of graphene oxide (1-5 layers) and 5.9 mg of carbon nanotubes (tube diameter 10-20 nm, tube length 5-15 μm) in deionized water and ultrasonically dispersing them for 3 h; then adding 88.5 mg of sodium hydroxide and stirring for 5 h to perform etching treatment so that the graphene oxide and the carbon nanotubes have etched holes, centrifuging and washing, to prepare etched graphene oxide and etched carbon nanotubes;
[0155] (2) 154 mg of ammonium tetrathiomolybdate was placed in deionized water, stirred for 3 h, and then 46 mg of thiourea and 37 mg of polyvinyl pyrrolidone were added, and stirred for 3 h to prepare a molybdenum disulfide precursor solution;
[0156] (3) placing the etched graphene oxide and the etched carbon nanotubes in step (1) in deionized water and stirring for 3 h, then mixing with the molybdenum disulfide precursor solution in step (2), dropping 0.1 mol / L dilute sulfuric acid, adjusting the pH to 3, and preparing an acidified precursor solution;
[0157] (4) The acidified precursor solution of step (3) was poured into a reaction kettle, and a hydrothermal reaction was carried out at 220° C. for 8 h to obtain a black solid; the black solid was washed with deionized water three times, and then freeze-dried at -45° C. for 24 h to prepare a negative electrode active material.
[0158] Test Case
[0159] The negative electrode active materials, conductive carbon black and PVDF glue prepared in the examples and comparative examples were mixed in a mass ratio of 8:1:1, and ground for 3 hours until the glue was viscous and transparent to obtain a black colloid; the black colloid was coated on a copper foil, dried at 100°C for 12 hours, and then cut into 16mm diameter discs as negative electrode sheets. 2 , AC:SP:PVDF mass ratio of 8:1:1) was cut into 14mm diameter discs as positive electrode sheets. Polypropylene Celgard2500 was used as the diaphragm, lithium hexafluorophosphate salt solution (lithium hexafluorophosphate concentration of 1 mol / L, solvent DMC, EMC, EC volume ratio of 1:1:1) was used as the electrolyte, and CR2025 button cells were assembled in a glove box. The water and oxygen concentrations in the glove box were ≤0.1ppm.
[0160] The assembled button cell was subjected to constant current charge and discharge test using a BlueDian charge and discharge test system (CT2001A). The electrochemical data obtained are shown in Table 1.
[0161] Table 1
[0162]
[0163] The test results in Table 1 show that the negative electrode plates of lithium ion capacitors prepared by the technical solution of the present application in Examples 1 to 3 have excellent electrochemical properties. The superiority of its performance is mainly due to the fact that the molybdenum disulfide layer contains nitrogen-doped carbon, and the molybdenum disulfide is loaded on reduced graphene oxide. The sheet structure of reduced graphene oxide also contains a three-dimensional network structure formed by cross-linking of carbon nanotubes. This improves the structural stability and conductivity of the composite material, and inhibits the volume expansion of molybdenum disulfide during the battery charging and discharging process. The electrochemical performance of the lithium ion capacitor prepared by the negative electrode is outstanding: at power densities of 0.2kW / kg and 20kW / kg, it can release a large energy density, and can stably cycle more than 5000 times at a high current density of 2A / g, and the coulombic efficiency of the 5000th cycle is above 97%.
[0164] In Comparative Example 1, no etching treatment was performed, resulting in fewer defects in reduced graphene oxide and carbon nanotubes, which did not contain etching holes, reducing the active sites of the negative electrode active material; in Comparative Example 2, heat drying treatment was used, resulting in the escape of PVP inserted between the molybdenum disulfide sheets, reducing the interlayer spacing; and the three-dimensional structure of graphene oxide and carbon nanotubes was also affected, which was not conducive to maintaining the structure of the negative electrode active material; in Comparative Example 3, no carbonization treatment was performed, at this time, PVP was still inserted between the molybdenum disulfide sheets, and the carrier of the supported molybdenum disulfide was graphene oxide. This makes the negative electrode active materials of Comparative Examples 1 to 3 above not conducive to improving their electrochemical performance.
[0165] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0166] The above-described embodiments only express several implementation methods of the present application, which is convenient for understanding the technical solution of the present application in detail, but it cannot be understood as limiting the scope of protection of the invention patent. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present application, several modifications and improvements can be made, which all belong to the scope of protection of the present application. It should be understood that the technical solutions obtained by those skilled in the art through logical analysis, reasoning or limited experiments on the basis of the technical solutions provided in the present application are all within the scope of protection of the claims attached to the present application. Therefore, the scope of protection of the patent of this application shall be based on the content of the attached claims, and the description can be used to interpret the content of the claims.
Claims
1. A negative electrode active material, characterized in that: Includes supported molybdenum disulfide and carbon nanotubes; The supported molybdenum disulfide comprises a reduced graphene oxide carrier and modified molybdenum disulfide supported on the reduced graphene oxide carrier, wherein the modified molybdenum disulfide comprises molybdenum disulfide and nitrogen-doped carbon, the molybdenum disulfide has a layered structure, and the nitrogen-doped carbon is inserted between the layers of the molybdenum disulfide; Among them, at least part of the interlamellar space of the supported molybdenum disulfide is filled with the carbon nanotubes; the reduced graphene oxide carrier and the carbon nanotubes have etched holes.
2. The negative electrode active material according to claim 1, characterized in that The carbon nanotubes filled between the sheets of the supported molybdenum disulfide form a three-dimensional network structure, and the three-dimensional network structure is formed by a plurality of carbon nanotubes entangled with each other. Wherein, the three-dimensional network structure of the carbon nanotubes is located between the sheets of the reduced graphene oxide carrier.
3. The negative electrode active material according to claim 1, characterized in that The etched holes of the reduced graphene oxide carrier are obtained by etching the reduced graphene oxide or graphene oxide with an etchant; and / or, The etched holes of the carbon nanotubes are obtained by etching the carbon nanotubes with an etchant.
4. The negative electrode active material according to any one of claims 1 to 3, characterized in that: The negative electrode active material has one or more of the following characteristics: (1) The diameter of the carbon nanotubes is 10 nm to 20 nm, and the length of the carbon nanotubes is 5 μm to 15 μm; (2) The number of layers of the reduced graphene oxide carrier is 1 to 5; (3) The pore volume of the negative electrode active material is 0.1 cm 3 / g~0.5cm 3 / g; (4) The specific surface area of the negative electrode active material is 30 m 2 / g~90m 2 / g; (5) The pore size of the negative electrode active material is 1 nm to 100 nm.
5. A method for preparing a negative electrode active material according to any one of claims 1 to 4, characterized in that: The following steps are involved: Mixing graphene oxide, carbon nanotubes and an etchant in a first solvent, and performing etching treatment so that the graphene oxide and the carbon nanotubes have etched holes, thereby preparing a modified carbon material; Mixing a molybdenum source, a sulfur source and a carbon-containing surfactant in a second solvent to prepare a molybdenum disulfide precursor solution; The modified carbon material and the molybdenum disulfide precursor solution are mixed, and the pH is adjusted to 2 to 4 to prepare an acidified precursor solution; The acidified precursor solution is subjected to a hydrothermal reaction, and after freeze-drying, a composite material to be carbonized is prepared; the composite material to be carbonized comprises a supported molybdenum disulfide precursor and carbon nanotubes; the supported molybdenum disulfide precursor comprises a graphene oxide carrier and a modified molybdenum disulfide precursor supported on the graphene oxide carrier, the modified molybdenum disulfide precursor comprises molybdenum disulfide and a carbon-containing surfactant, the molybdenum disulfide has a layered structure, and the carbon-containing surfactant is inserted between the layers of the molybdenum disulfide; at least part of the interlamellar space of the supported molybdenum disulfide is filled with carbon nanotubes; The composite material to be carbonized is subjected to carbonization treatment in a nitrogen atmosphere, so that the graphene oxide is converted into reduced graphene oxide, and the carbon-containing surfactant is converted into nitrogen-doped carbon, so as to prepare the negative electrode active material.
6. The method for preparing the negative electrode active material according to claim 5, characterized in that: The steps of preparing the molybdenum disulfide precursor solution meet one or more of the following characteristics: (1) The molybdenum source includes ammonium tetrathiomolybdate, (2) The sulfur source includes thiourea; (3) The carbon-containing surfactant includes polyvinyl pyrrolidone; (4) The mass ratio of the molybdenum source, the sulfur source and the carbon-containing surfactant is (145-160): (40-50): (30-45).
7. The method for preparing the negative electrode active material according to claim 5, characterized in that: The preparation method has one or more of the following characteristics: (1) The process parameters of the hydrothermal reaction include: a reaction temperature of 200° C. to 220° C.; (2) The freeze-drying process parameters include: a temperature of -45°C to -20°C; (3) The process parameters of the carbonization treatment include: a reaction temperature of 830°C to 870°C; (4) The diameter of the carbon nanotube is 10 nm to 20 nm, and the length of the carbon nanotube is 5 μm to 15 μm; (5) The etchant includes one or more of sodium hydroxide and potassium hydroxide; (6) The mass ratio of the graphene oxide, the carbon nanotubes and the etchant is (22-26): (2-12): (80-95).
8. A negative electrode plate, characterized in that: It comprises a negative electrode current collector and a negative electrode active material layer stacked on the surface of the negative electrode current collector, wherein the negative electrode active material layer comprises the negative electrode active material according to any one of claims 1 to 4; wherein, in terms of mass percentage, the negative electrode active material accounts for 70% to 85% of the negative electrode active material layer.
9. A secondary battery or capacitor, characterized in that: It comprises a negative electrode, a positive electrode, a separator between the negative electrode and the positive electrode, and an electrolyte; wherein the negative electrode is the negative electrode sheet according to claim 8; The secondary battery is a lithium ion battery, a sodium ion battery, a potassium ion battery, a calcium ion battery, a magnesium ion battery or a zinc ion battery; The capacitor is a lithium ion capacitor, a sodium ion capacitor, a potassium ion capacitor, a calcium ion capacitor, a magnesium ion capacitor or a zinc ion capacitor.
10. An electric energy storage system, characterized in that: An energy storage unit is included, the energy storage unit comprising the capacitor of claim 9.
Citation Information
Cited By
Thin-layer metal phase tungsten disulfide positive electrode material for high-rate zinc ion battery and preparation method and application of electrode
CN120023333A
A thin-layer metal-phase tungsten disulfide positive electrode material for high-rate zinc ion batteries, a preparation method and application thereof
CN120023333B
Modified molybdenum trioxide electrode material and preparation method thereof
CN120236913A